Remote Management Information Systems In Tax Consulting Operations And Client Relations: Sistem Informasi Manajemen Jarak Jauh Dalam Operasional Konsultan Pajak Dan Hubungan Klien - Reza Tri Anngara; Dewi Andriani (Proceedings of The ICECRS, 2024)
General Background In the current digital era, the success of organizations depends heavily on robust management information frameworks and communication to navigate dynamic regulations and user expectations. Specific Background The Andrean Hermawan office faces operational challenges where staff must conduct physical visits to control web-based applications, consuming considerable time and operational costs. Knowledge Gap Current practices lack the integration of distance-control platforms to overcome geographical barriers and mitigate frequent misinterpretations during consultations. Aims This study explores the application of integrated technology and communication platforms to optimize service quality. Results The implementation of the AnyDesk software allows staff to distantly control applications and demonstrate solutions in real-time, significantly minimizing physical visits and reducing operational expenditures. Furthermore, direct demonstrations through this platform resolve communication misunderstandings, ensuring accurate interpretation of documents. Novelty This research demonstrates the specific utility of distance software as a dual-function tool for technical administration and transparent communication within a localized consulting context. Implications Prioritizing integrated technology and digital communication strategies provides a significant competitive advantage by optimizing efficiency and satisfaction. Highlights:  Utilizing AnyDesk software minimizes physical visits and significantly reduces business expenditures. Real-time technical administration solves geographical distance barriers during advisory processes. Direct visual demonstrations clear up misunderstandings and ensure accurate message delivery. Keywords: AnyDesk Application, Operational Cost, Communication Strategy, Real Time Administration, Distance Software